2021
DOI: 10.1002/aur.2647
|View full text |Cite
|
Sign up to set email alerts
|

Impaired attentional bias toward one's own face in autism spectrum disorder: ERP evidence

Abstract: Converging lines of evidence seem to indicate reduced self‐referential processing in individuals with autism spectrum disorder (ASD). However, processing of one's own face has rarely been investigated in the context of ASD. Thus, the aim of the present study was to elucidate the role of attentional biases in the processing of self‐ and other faces in ASD. To achieve this goal we presented participants with images of their own face, the face of a close‐other, and famous and unknown faces in a Stroop‐like paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 55 publications
4
10
0
Order By: Relevance
“…Such an effect was also repeatedly found for one’s own face when compared to a close-other’s face, if—similarly to the present study—the close-other was freely selected by participants as their most significant person ( Cygan et al. 2014 ; Kotlewska and Nowicka 2015 ; Cygan et al. 2021 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Such an effect was also repeatedly found for one’s own face when compared to a close-other’s face, if—similarly to the present study—the close-other was freely selected by participants as their most significant person ( Cygan et al. 2014 ; Kotlewska and Nowicka 2015 ; Cygan et al. 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…2017 ) and late ERP components, especially P3—a positive ERP component with centro-parietal distribution and latency of 300 ms or longer ( Cygan et al. 2014 ; Kotlewska and Nowicka 2015 ; Cygan et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to ensure control over gender-related effects, the gender of close-other faces has to be matched with that of the participant. This selection approach has been consistent with earlier studies (e.g., Tacikowski et al, 2011Tacikowski et al, , 2013Cygan et al, 2014;Nowicka, 2015, 2016;Kotlewska et al, 2017;Nijhof et al, 2018;Cygan et al, 2022;Żochowska et al, 2022Amodeo et al, 2023). Among the participants, 23 individuals opted for a friend, 9 for their sibling, and 3 for their partner as their chosen close-other.…”
Section: Stimulisupporting
confidence: 80%
“…As humans are the subject of their own cognition, they are in the unique position of possessing years of detailed motor and sensory-feedback experiences about themselves which result in a highly-elaborated (not only visual but also multimodal) representation of the self-face 7 . Self-face recognition has been shown to be impaired in a variety of neurological or developmental disorders such as autism 8 10 and schizophrenia 11 13 . In children suffering from autistic-spectrum disorders, mirror self-recognition is developmentally delayed and, in some cases, even absent 14 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies showed that initial indications of self-face discrimination, distinguishing between one’s own face and others, occur outside visual areas. This is manifested by a reduction in midfrontal N2 for one’s own face 39 , 40 , 49 , 51 53 or as an increase of P3 in central-parietal areas 9 , 10 , 41 , 45 , 49 , 50 , 53 56 . An increase of the midfrontal N2 often signifies a more pronounced involvement of certain forms of executive control 57 .…”
Section: Introductionmentioning
confidence: 99%